THERAPEUTIC MEETINGS WITH CHILDREN AND FAMILY MEMBERS: TREATING PATHS TO PROMOTE CHILDREN’S MENTAL HEALTH - Porfirio Carvalho, Larissa; Ligia Gonçalves de Araújo Ferreira, Carlina; Miranda Ribeiro de Melo, Andréa; Carolina Salustino, Maria; Allyson Gomes Ferreira, Jefferson (Health and Society, 2023)
In Primary Health Care (PHC), the matrix can conform through the relationship between Family Health teams (SF teams) and Expanded Centers for Family Health and Primary Care (NASF-AB). The aim of the study is to report the experience of NASF-AB assistance to a group of children aged 6 to 12 years old with behavioral changes, anxiety disorders and emotional problems. Anxiety disorders are among the most common psychiatric illnesses in children and adolescents.